Governing-through-Harm and Public Goods Policing. Issue 1 (September 2018) - Berg, Julie; Shearing, Clifford
Among scholars of law and crime and practitioners of public safety, there is a pervasive view that only the public police can or should protect the public interest. Further, the prevailing perception is that the public police predominantly governs through crime—that is, acts on harms as detrimental to the public good. We argue that governing harm through crime is not always the most effective way of producing public safety and security and that the production of public safety is not limited to public police forces. An approach of governing-through-harm that uses a variety of noncrime strategies and private security agents as participants in public safety is often more effective—and more legitimate—than the predominant governing-through-crime approach. We reflect on case studies of noncrime intervention strategies from the Global South to bolster the case for decoupling the link between the public police and public goods. A new theoretical framing needs to be pursued.